Emerging roles of microRNAs in pancreatic cancer diagnosis, therapy and prognosis (Review) - SUBRAMANI, RAMADEVI (Int J Oncol, 2015)
Pancreatic cancer is one of the leading causes of cancer related death. Increasing incidence and mortality indicates a lack of detection and post diagnostic management of this disease. Recent evidences suggest that, miRNAs are very attractive target molecules that can serve as biomarkers for predicting development and progression of pancreatic cancer. Furthermore, miRNAs are also promising therapeutic targets for pancreatic cancer. The objective of the present review is to discuss the significance of miRNA in pancreatic cancer development, diagnosis, therapy and prognosis. We extracted and compiled the useful information from PubMed database, which satisfied our criteria for analysis of miRNAs in pancreatic cancer diagnosis, therapy and prognosis. A summary of the most important miRNAs known to regulate pancreatic tumorigenesis is provided. The review also provides a collection of evidence that show miRNA profiles of biofluids hold much promise for use as biomarkers to predict and detect development of pancreatic cancer in its early stages. Identification of key miRNA networks in pancreatic cancer will provide long-awaited diagnostic/therapeutic/prognostic tools for early detection, better treatment options, and extended life expectancy and quality of life in PDAC patients.